2009
DOI: 10.1038/jcbfm.2008.168
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stem Cell Factor and Granulocyte-Colony Stimulating Factor in Brain Repair during Chronic Stroke

Abstract: Chronic stroke is a highly important but under-investigated scientific problem in neurologic research. We have reported earlier that stem cell factor (SCF) in combination with granulocyte-colony stimulating factor (G-CSF) treatment during chronic stroke improves functional outcomes. Here we have determined the contribution of bone marrow-derived cells in angiogenesis and neurogenesis, which are enhanced by SCF+G-CSF treatment during chronic stroke. Using bone marrow tracking, flow cytometry, 2-photon live brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 41 publications
(56 reference statements)
6
44
2
Order By: Relevance
“…Our previous work revealed that SCF + G-CSF treatment in chronic stroke increased the blood vessel density in the cortex adjacent to the infarct cavity (Piao et al, 2009). Stoltz et al (1996) reported that NF-κB crucially regulated angiogenesis.…”
Section: Scf In Combination With G-csf Treatment In Chronic Stroke Inmentioning
confidence: 98%
See 2 more Smart Citations
“…Our previous work revealed that SCF + G-CSF treatment in chronic stroke increased the blood vessel density in the cortex adjacent to the infarct cavity (Piao et al, 2009). Stoltz et al (1996) reported that NF-κB crucially regulated angiogenesis.…”
Section: Scf In Combination With G-csf Treatment In Chronic Stroke Inmentioning
confidence: 98%
“…We have demonstrated that systemic administration of SCF + G-CSF in the chronic phase of stroke enhances neuronal activity in the ipsilesional somatosensorimotor cortex and induces a stable and long-lasting functional improvement when compared to SCF or G-CSF alone (Zhao et al, 2007). Moreover, SCF + G-CSF treatment in chronic stroke also promotes neuronal network remodeling and blood vessel formation in the peri-infarct cortex Piao et al, 2009). However, how SCF + G-CSF treatment rebuilds neuronal and vascular networks in the chronic stroke brain remains unclear.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…18 Likewise, administration of G-CSF alone or in combination with stem cell factor during chronic stroke improves functional outcomes, possibly by facilitating the proliferation of endogenous neural stem cells and enhancing cytokine-induced generation of neuronal cells from bone marrow-derived cells. 19,20 G-CSF treatment was recently shown to induce substantially more neural progenitor cells and immature neurons in subcortical regions adjacent to the infarcted area. G-CSF also increased neurogenesis in the dentate gyrus of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…They may also originate from the immature cells in the local environment in the brain. Pericytes are considered to possess multipotent activity and are able to differentiate into different lineages similar to MSCs (Piao et al 2009). Pericytes may promote tissue repair by a balance between active angiogenesis under scarce pericytes and vessel maturation by rich pericyte coverage.…”
Section: Angiogenesis After Strokementioning
confidence: 99%